Edukacja, język i tożsamość etniczna Inuitów na Grenlandii - Gmerek, Tomasz (Wydawnictwo Naukowe UAM, 2013)
The article deals with the issue of the relation between education and the processes of the development of ethnic identity in Greenland. Particular emphasis was placed on reconstructing educational practices and the language policy implemented toward the Inuit in Greenland. An attempt was made at examining the relationship between the Danish language policy, schooling, and development of ethnic identity of the Inuit in Greenland.
Education, Language and Inuit Ethnic Identity in Greenland
Keywords: education; ethnic identity; language; history; Inuit; Greenland